A Donor‐Stabilized Zwitterionic "Half‐Parent" Phosphasilene and Its Unusual Reactivity towards Small Molecules. Issue 7 (16th January 2014) - Hansen, Kerstin; Szilvási, Tibor; Blom, Burgert; Irran, Elisabeth; Driess, Matthias
Abstract The stabilization of the labile, zwitterionic "half‐parent" phosphasilene 4 L′SiPH (L′=CH[(CCH2)CMe(NAr)2]; Ar=2, 6‐iPr2C6H3) could now be accomplished by coordination with two different donor ligands (4‐dimethylaminopyridine (DMAP) and 1, 3, 4, 5‐tetramethylimidazol‐2‐ylidene), affording the adducts 8 and 9, respectively. The DMAP‐stabilized zwitterionic "half‐parent" phosphasilene 8 is capable of transferring the elusive parent phosphinidene moiety (:PH) to an unsaturated organic substrate, in analogy to the "free" phosphasilene 4. Furthermore, compounds 4 and 8 show an unusual reactivity of the SiP moiety towards small molecules. They are capable of adding dimethylzinc and of activating the SH bonds in H2S and the NH bonds in ammonia and several organoamines. Interestingly, the DMAP donor ligand of 8 has the propensity to act as a leaving group at the phosphasilene during the reaction. Accordingly, treatment of 8 with H2S affords, under liberation of DMAP, the unprecedented thiosilanoic phosphane LSiS(PH2) 16 (L=HC(CMe[2, 6‐iPr2C6H3N])2). Compounds 4 and 8 react with ammonia both affording L′Si(NH2)PH217, respectively. In addition, the reaction of 8 with isoproylamine, p‐toluidine, and pentafluorophenylhydrazine lead to the corresponding phosphanylsilanes L′Si(PH2)NHR (R=iPr 18 a; R=C6H5CH318 b, R=NH(C6F5) 18 c), respectively.